Characterization of GPR101 transcript structure and expression patterns. (August 2016) - Trivellin, Giampaolo; Bjelobaba, Ivana; Daly, Adrian F; Larco, Darwin O; Palmeira, Leonor; Faucz, Fabio R; Thiry, Albert; Leal, Letícia F; Rostomyan, Liliya; Quezado, Martha; Schernthaner-Reiter, Marie Helene; Janjic, Marija M; et al.
Abstract : We recently showed that Xq26.3 microduplications cause X-linked acrogigantism (X-LAG). X-LAG patients mainly present with growth hormone and prolactin-secreting adenomas and share a minimal duplicated region containing at least four genes. GPR101 was the only gene highly expressed in their pituitary lesions, but little is known about its expression patterns. In this work, GPR101 transcripts were characterized in human tissues by 5′-Rapid Amplification of cDNA Ends (RACE) and RNAseq, while the putative promoter was bioinformatically predicted. We investigated GPR101 mRNA and protein expression by RT-quantitative PCR (qPCR), whole-mount in situ hybridization, and immunostaining, in human, rhesus monkey, rat and zebrafish. We identified four GPR101 isoforms characterized by different 5′-untranslated regions (UTRs) and a common 6.1kb long 3′UTR. GPR101 expression was very low or absent in almost all adult human tissues examined, except for specific brain regions. Strong GPR101 staining was observed in human fetal pituitary and during adolescence, whereas very weak/absent expression was detected during childhood and adult life. In contrast to humans, adult monkey and rat pituitaries expressed GPR101, but in different cell types. Gpr101 is expressed in the brain and pituitary during rat and zebrafish development; in rat pituitary, Gpr101 is expressed only after birth and shows sexual dimorphism. This study shows that different GPR101 transcripts exist and that the brain is the major site of GPR101 expression across different species, although divergent species- and temporal-specific expression patterns are evident. These findings suggest an important role for GPR101 in brain and pituitary development and likely reflect the very different growth, development and maturation patterns among species.